The Psychometric Properties of the Norwegian version of Parenting Stress index, 3. version (PSI) - Kornør, Hege; Martinussen, Monica (PsykTestBarn, 2011)
Description: The Parenting Stress Index (PSI) is a questionnaire for measuring stress in the parent-child relationship. The total level of stress is assessed by seven parent characteristic scales and six child characteristic scales. In addition, there is one life stress scale. The target group is parents of children up to 12-years old. It takes 20-25 minutes to complete the questionnaire. The Norwegian translation by John A. Rønning is based on the American third edition of the PSI, developed by Richard A. Abidin in 1995. It is necessary to obtain a user’s license from PAR inc., USA, in order to purchase and use the PSI. The availability of the Norwegian version is unclear. Literature search: Our systematic literature search for psychometric evidence for the Norwegian version of the PSI returned 41 references, of which three met the inclusion criteria. We included two additional articles suggested by experts. Psychometrics: The included publications reported data from three Norwegian studies with a total of 1096 participants. The search for evidence for the Swedish and Danish PSI versions did not identify any publications. The included publications reported mean scores for postpartum women, group differences and internal consistency (median Cronbach’s alpha > 0.90) Conclusion: The evidence base for the Norwegian PSI norms is based on a population that is too homogenous to be applicable for others than postpartum women. Expected group differences provide support for the construct validity of the test, but there is so far insufficient evidence to make any firm conclusions regarding the construct validity. There is no evidence for criterion- related validity. The Norwegian version of the PSI has excellent internal consistency. The available evidence is not sufficient to assess the total applicability of this instrument. Future research with and on the PSI should focus on psychometric research questions.